Strategi Pengembangan dan Tantangan Bisnis dalam Menjangkau Konsumen Generasi Z : (Studi Kasus Brand Hijab Leenavie.id) - Bilqis Nabila Istiqlaliani; Agung Winarno; Wening Patmi Rahayu (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The development of digital technology has greatly influenced consumer behavior, particularly among Generation Z, who are dominant in Indonesia's hijab fashion market. This shift requires businesses to adapt their strategies to meet the dynamic, trend-driven, and digitally-savvy preferences of young consumers. This study examines the business development strategy of Leenavie.id, a hijab brand, and the challenges it faces in targeting Generation Z. Using a qualitative approach with case study methodology, in-depth interviews with business owners were conducted to gain insights into the business development process. The findings show that Leenavie.id focuses on product innovation, competitive pricing, social media as a primary distribution and promotion channel, and leveraging e-WOM for brand awareness and emotional connections with consumers. Success indicators include a high repeat order rate, positive market response, and external collaboration offers. However, challenges such as limited capital, small production capacity, and underutilization of the marketplace hinder scalability. The study suggests that enhancing digital adaptation, strengthening operational capacity, and fostering strategic collaborations are key to improving the competitiveness and sustainability of local hijab businesses. Future research should include consumer perspectives for a more comprehensive understanding of customer behavior and loyalty.